2022
DOI: 10.1177/23259671221094848
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Nanofiber Resorbable Scaffold During Rotator Cuff Repair: Surgical Technique and Results After Repair of Small- to Medium-Sized Tears

Abstract: Background: The rate of retear after primary rotator cuff failure remains unacceptably high (up to 36% for small- to medium-sized tears). Augmentation of cuff repair with scaffold devices has been reported to improve healing after cuff repair. Purpose/Hypothesis: To describe the surgical technique of using an interpositional nanofiber scaffold during rotator cuff repair and report on a retrospective series of patients regarding functional outcomes and postoperative healing on magnetic resonance imaging (MRI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A recently published study reported on a retrospective cohort of patients undergoing arthroscopic rotator cuff repair with an interpositional scaffold. 7 The study showed a 9% rate of failure, primarily in the setting of large or massive tear patterns, which are known to be associated with increased rates of failure. 2 , 3 When small- to medium-sized tears, which comprised most of this cohort, were segregated, a 97% healing rate was noted based on postoperative magnetic resonance imaging analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recently published study reported on a retrospective cohort of patients undergoing arthroscopic rotator cuff repair with an interpositional scaffold. 7 The study showed a 9% rate of failure, primarily in the setting of large or massive tear patterns, which are known to be associated with increased rates of failure. 2 , 3 When small- to medium-sized tears, which comprised most of this cohort, were segregated, a 97% healing rate was noted based on postoperative magnetic resonance imaging analysis.…”
Section: Discussionmentioning
confidence: 97%
“…It has shown promising early results in both animal and human studies. 7 , 8 The purpose of this article is to describe the technique for use of this interpositional nanofiber scaffold in the setting of an arthroscopic rotator cuff repair.…”
mentioning
confidence: 99%
“…Meanwhile, as a synthetic scaffold, it can decrease inflammatory reaction and cause less scarring at the fibrocartilaginous enthesis than biological scaffolds. 99 In a rabbit model of anterior fork ligament injury, the researchers wrapped biomimetic nanofiber membranes around autologous hamstring tendons. Eight weeks after surgery, they found that the biomimetic nanofibrous membrane formed new bone tissue between the tendon and bone, possibly because its biodegradable nanofibrous membrane facilitated the penetration of bone tissue into the fibrocartilaginous enthesis and promoted bone formation.…”
Section: Nanofibrous Scaffolds For the Healing Of Fibrocartilaginous ...mentioning
confidence: 99%
“…The scaffold has an ECM biomimetic structure, which contributes to a likely mechanism that promotes a healing response similar to natural tissue. [97][98][99] During the operation, doctors insert absorbable nanofibrous scaffolds into the suture line between the bone and tendon, and use double-row repair technology to insert nanofibrous scaffolds between the bone and tendon. 99 When the inner end of the fibrocartilage is broken, the Rotiumt scaffold can promote its healing and improve its strength.…”
Section: Nanofibrous Scaffolds For the Healing Of Fibrocartilaginous ...mentioning
confidence: 99%
See 1 more Smart Citation